Understanding health inequalities: how does socioeconomic deprivation impact on mortality for interstitial lung disease-related hospital admissions? - Laura White; Jonathan Shaw; Bethan Powell; Nyan May Kyi; Rebecca Huang; Emma Hardy; Dilanka Tilakaratne; Gareth Hughes; Conal Hayton; Trishala Raj; Georges Ng Man Kwong; Amy Gadoud; et al. (Clinical Medicine)
Introduction: Interstitial lung diseases (ILD) represent a heterogenous group of conditions affecting the lung parenchyma. A proportion develop a progressive phenotype, but the disease is unpredictable and accompanied by significant unmet needs.1 Patients with ILD are at risk of hospital admissions secondary to a wide range of aetiology, including respiratory decompensation.2 Socioeconomic deprivation in ILD has been associated with prolonged time to diagnosis and reduced overall survival, but little has been studied within the acute admission setting.3 We sought to determine mortality associated with ILD-related hospital admissions and understand the role of deprivation in mortality outcomes. Materials and Methods: We undertook a multi-centre retrospective observational cohort study of International Classification of Diseases (ICD)-10-coded ILD primary admissions ≥18-years old between 1 January 2017 and 31 December 2019 across six NHS trusts in north-west England. Primary outcome was time to death from first day of hospital admission. Deprivation was determined by the 2019 English Indices of Deprivation, where decile 1 represents the most deprived and 10 the least.4 Primary outcome was the number of days from admission to death. For the purposes of Kaplan–Meier analysis, deprivation deciles (DDs) were grouped into quintiles. Results and Discussion: 740 admissions were included in analysis. Mean and median DD scores were 4.80 and 4, respectively. 28.4% (210/740) of admissions were observed in DDs 1 and 2 (the most deprived). We observed an overall 15.4% inpatient and 39.2% 90-day all-cause mortality. Kaplan–Meier survival analysis comparing deprivation quintiles showed no statistical difference in overall survival across the entire follow-up period (p=0.061). In a multivariate Cox-regression analysis of inpatient mortality, the DD hazard ratio was 1.069 but not statistically significant (p=0.064). Main factors associated with inpatient mortality were pre-admission long-term oxygen therapy (hazard ratio (HR) 2.128, p<0.001) and being treated for acute exacerbation of ILD (HR 1.909, p=0.010).To the best of our knowledge, this is the first dataset assessing the impact of socioeconomic deprivation on acute ILD admission outcomes. Our data further support the notion that hospitalisation events have a significant role in ILD mortality.5 Our results also show similar admission-related mortality outcomes to a previous UK regional real-world dataset.6 Conclusion: In this real-world dataset of ILD-related hospital admissions, lower socioeconomic deprivation, as determined by the English Indices of Deprivation, was not associated with higher mortality outcomes. However, overall all-cause mortality remained universally high. Prospective, larger-scale studies are required to validate these results and further understand this relationship in acute ILD-related admissions.